(untitled) (Pedagogy of Higher and Secondary Education, 2011)
A multimedia didactic game as special mean of development of such properties of student’s creative personality as formal perception, generalization of mathematical material and flexibility of thought in extracurricular work on mathematics is considered in the article. The types of tasks, included in the structure of such multimedia games are described.